The ‘Nibble fish’, Garra rufa (Heckel, 1843), as a potential candidate species for ecotourism in North-East India - Shil, Bikash; Lahiri, Biswajit; Ghosh, Amitava; Radhakrishnan, Kizhakke Veettil; Pandey, Pramod Kumar (Journal of the Inland Fisheries Society of India, 2021)
The farming sector in India has been passing through a structural metamorphosis and confronting obvious challenges of drastic reduction in the number of farmers (7.1%), and an increase in numbers of wage earners (3.5%) over a decade from 2001 to 2011 (Census of India, 2011; Sood, 2015). There will be an inevitable impact on farm production in the country shortly if this trend continues. Probably, the most pragmatic solution to this crisis is to make the farm business a profitable and economic venture and to attract farmers and rural youth to farming and farm business for a sustainable agrarian economy